Changing traditions : al-Mubarrad's refutation of Sībawayh and the subsequent reception of the Kitāb - Bernards, Monique (Studies in Semitic languages and linguistics, 1997)
This study deals with the development of Arabic linguistics as a distinct Islamic science. The period covered ranges from the founding father of Arabic grammar, Sībawayh, up through the classical era focusing on the grammarian al-Mubarrad (d. 285 AH/898 AD). The reader is introduced to the environment in which Arabic grammar evolved. Subsequently, al-Mubarrad's position vis-à-vis Sībawayh and other contemporary grammarians is analyzed in depth and, finally, his decisive role in the development of Arabic linguistics is discussed. Those interested in the intellectual history of early Islam will benefit from the study since it revises current interpretations on the development of Arabic grammar and questions the historicity of the so-called \'grammatical schools\'. A separate edition of the oldest extant commentary on the Kitāb Sībawayh , by Ibn Wallād (d.332 AH/943 AD), is included.